An Overview of «Umdet ul-Ahbar» by Abdulgaffar Qirimi » - I.М. Mirgaleev; Derya Derin Paşaoğlu (Золотоордынское обозрение)
The article reviews the manuscript book of Abdulgaffar Qirimi by the name of «Umdet ul-Ahbar» («The Support of Communications»). This work is written in Ottoman language according to the tradition of Ottoman historical writings. Authors of the article briefly recount Abdulgaffar Qirimi’s information contained in his work and dedicated to Genghis Khan, the Golden Horde, and the Crimean Khanate. Recently in Kazan have been published the facsimile and transcription of this work. Therefore, the authors decided to introduce into scholarly circulation the Russian summary of this work (the work being translated into Russian). Using a continuous method, the authors have made an overview of the main political events mentioned in the book. This information will be useful for the specialists studying the history of the Golden Horde and Tatar khanates. The importance of this source is beyond any doubt since Abdulgaffar Qirimi reports many original details and, especially for the 18th century, his information is authentic and based on personal observations. The manuscript book consists of several parts. It contains information about world history, the history of the prophets, the history of the Seljuks and Ottomans. The main part of the work is devoted to the Golden Horde (starting from Genghis Khan and his descendants), Crimean Khanate, Girayids and murzas. Abdulgaffar Qirimi sought to write a history of the descendants of Jochi khan. He used in his book more than 20 historical works. Abdulgaffar Qirimi reports the names of these works and indicates where he got this or that information. At the same time, he had access to the archives of the Crimean Khanate and used his family legends as well as popular traditions. Plenty of space in his work occupy his own observations as of a participant in military campaigns and court life. Although Abdulgaffar Qirimi makes some mistakes, however his work contains a complete history of the Golden Horde. His information concerning khans Berke, Tokhta, Uzbek, Tokhtamysh, and Ulugh Muhammad reflects the «popular version» and is based on oral historiology of the Tatars. Extensive information about the Crimean Khanate and the State structure of khanate are sufficiently original. In addition, a question of the spread of Islam among Tatars is considered in some detail and largely confirmed by other sources.